Appetite self-regulation declines across childhood while general self-regulation improves: A narrative review of the origins and development of appetite self-regulation. (1st July 2021) - Russell, Alan; Russell, Catherine G.
Abstract: This narrative review discusses the origins and development of appetite self-regulation (ASR) in childhood (from infancy to age 6 or 7 years). The origins, or foundations, are the biological infrastructure associated with appetite regulation and appetite self-regulation. Homeostatic regulation in infancy is examined and then evidence about developmental change in components of ASR. The main ASR-related components covered are: delay-of-gratification, caloric compensation, eating in the absence of hunger, food responsiveness/hedonics and fussy eating. The research included behavioral measures, parent-reports of appetitive traits and fMRI studies. There were two main trends in the evidence: a decline across childhood in the components of ASR associated with food approach (and therefore an increase in disinhibited eating), and wide individual differences. The decline in ASR contrasts with general self-regulation (GSR) where the evidence is of an improvement across childhood. For many children, bottom-up automatic reactive processes via food reward/hedonics or food avoidance as in fussy eating, appear not to be matched by improvements in top-down regulatory capacities. The prominence of bottom-up processes in ASR could be the main factor in possible differences in developmental paths for GSR and ASR. GSR research is situated in developmental science with its focus on developmental processes, theory and methodology. In contrast, the development of ASR at present does not have a strong developmental tradition to access and there is no unifying model of ASR and its development. We concluded (1) outside of mean-level or normative changes in the components of ASR, individual differences are prominent, and (2) there is a need to formulate models of developmental change in ASR together with appropriate measurement, research designs and data analysis strategies.